Intragroup Conflict During Study Abroad - Bodycott, Peter (Journal of International Students, 2015)
Co-national groups of individuals from the same country can provide members with psychological and sociocultural support when coping with the stresses of studying abroad. This article examines intragroup task and relationship conflict that occurred in one co-national group during a 14-week short-term study abroad program. Findings reveal the negative effect of intragroup conflict, within the co-national group, on student’s personal and social −ethnic− identities, acculturation and program involvement. Recommendations are made about ways to help students in co-national groups cope with acculturation and intragroup conflict, and how institutions can better prepare and support students for study abroad.